Involving Youth in the Community Development Process - Rosemary V. Barnett; Mark A. Brennan (EDIS)
Recent trends suggest that youth are playing an increasingly important role in the development of their communities. FCS-9253, a 3-page fact sheet by Rosemary V. Barnett and M. A. Brennan, lists 8 general steps that planners can follow to assist youth in becoming leaders and active participants within their community. Includes references and additional reading. Published by the UF Department of Family Youth and Community Sciences, July 2006.